A Comment on Kaldor's Note - Kubota, K. (Review of Economic Studies, 1970)
Journal Article A Comment on Kaldor's Note Get access K. Kubota K. Kubota New York Office of the United Nations Conference on Trade and Development Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 1, January 1970, Page 9, https://doi.org/10.2307/2296493 Published: 01 January 1970 Article history Received: 01 October 1969 Published: 01 January 1970